Deteksi Protozoa Usus Oportunistik pada Penderita Diare Anak di Puskesmas Rawat Inap Pekanbaru - Esy Maryanti; Suri Dwi Lesmana; Hendro Mandela (Jurnal Ilmu Kedokteran, 2015)
Diarrhea is still a public health problem, especially in developing countries. Diarrhea causes morbidity and highmortality in children. Diarrhea can be caused by viruses, bacteria, parasites and food poisoning. One of the parasitethat can cause diarrhea is intestinal protozoa. Lately, attention to intestinal opportunistic protozoan infections isincreasing. Opportunistic intestinal protozoa infection is an infection by intestinal protozoa that had not consideredimportant and now can cause disease in humans. Cryptosporidium sp, Cyclospora cayetanensis, Isospora belii andBlastocystis hominis are opportunistic intestinal protozoa. The clinical manifestations of the infection depends on theimmune status of patients, ranging from asymptomatic in immunocompetent individuals to chronic diarrhea not curedand fatal in patients imunokompromis. This study aims to detect opportunistic intestinal protozoa in children withdiarrhea patients in health centers Inpatient Pekanbaru used modified acid fast stain procedure. A total of 76 samplestested positive obtained 22.3% of opportunistic intestinal protozoa found that 9.2% were infected with Cryptosporidiumsp, Cyclospora infection were 2.6% and Blastocystis hominis 10.5%, while Isospora not found.